Agro-industrial accidents linked to length of service, operation site and confidence in employer adherence to safety rules - Emmanuel Tamba Koroma; Jia Bainga Kangbai (BMC, 2020)
Abstract Background The agriculture sector consistently ranks among the most hazardous occupational industries globally with high risk of job-related injuries, illnesses, disability, and death. In 2015, the agricultural fatal work injury rate in the United States was 22.8 per 100,000 full-time equivalent workers; seven times the all-worker fatal injury rate of 3.4 per 100,000 full-time equivalent workers. In this study we identified the factors that are associated with workplace accident and injuries at the Goldtree (SL) Limited Company - a private international agro-industrial palm kernel oil company operating in eastern Sierra Leone. Methods This is a descriptive research that made use of both qualitative and quantitative research techniques to collect and analyse agro-industrial occupation-related accident and injuries of workers attached to the Goldtree (SL) Limited Company, an international palm kernel oil producing and marketing company in Sierra Leone. We analyzed the responses of 100 workers at the Goldtree (SL) Limited Company that are related to their work safety, adherence to work safety guidelines as well as working habit. Results Thirty nine (39.0%) of the workers interviewed in this study said they had been involved in some forms of occupational accident; (33.3%) of those involved in some form of occupational-related accidents have been working in the company for 3-5 years, 22.0% have been working at the company for at least 2 years; 7.7% have been working for 6-8 years (X2 = 9.88, p-value = 0.02). Conclusion Workers who have spent few years in the job, and those workers who have confidence that management is committed to addressing health and safety issues, believed that their working tools were in excellent condition, or agreed that they have the rights and responsibilities for an effective workplace health and safety system have decreased odds of experiencing occupational-related accidents or injury at the study site.